International Capital Markets Structure, Preferences and Puzzles: The US-China Case - Guglielmo Maria Caporale; Michael Donadelli; Alessia Varani (Center for Economic Studies and ifo Institute (CESifo), 2014)
A canonical two country-two good model with standard preferences does not address three classic international macroeconomic puzzles as well as two well-known asset pricing puzzles. Specifically, under financial autarky, it does not account for the high real exchange rate (RER) volatility relative to consumption volatility (RER volatility puzzle), the negative RER-consumption differentials correlation (Backus-Smith anomaly), the relatively low cross-country consumption correlation (consumption correlation puzzle), the low risk-free rate (risk-free rate puzzle) and the high equity risk premium (equity premium puzzle) in the data. In this paper, we show that instead a two country-two good model with recursive preferences, international complete markets and correlated long-run innovations can address all five puzzles for a relatively large range of parameter values, specifically in the case of the US and China. Therefore, in contrast to other IBC models, its performance does not rely on any financial market imperfections.
Keywords: F30; F40; 330; financial autarky; complete markets; long-run risk; anomalies